The effects of lactobacillus acidophilus on clinical improvement of common cold in children - Eka Sari Astuti; . Sumadiono; Amalia Setyati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Children contract an average of approximately six colds each year and irrational antibiotic has been prescribed to 60% of cases that potentially cause antibiotic resistency. Some studies in humans have shown that probiotic are effective in reducing the severity of common cold symptoms. The mechanisms of probiotic are attributed to an increase of the innate and acquired immune response. The aim of our study was to investigate whether the consumption of Lactobacillus acidophilus R0052 and Lactobacillus rhamnosus R0011 in dosage of 0.1 x 109 CFU and 1.9 x 109 CFU per day during 7 days influences the severity of symptoms of the common cold in children. This study can be described as a randomized, double-blind, placebo-controlled clinical trial. 100 children who developed symptoms of the common cold within 24-48 hours before enrollment were included in the study. Patients in the probiotic group (n=50) received probiotic capsules containing 0.1x109 of Lactobacillus acidophilus and 1.9x109 Lactobacillus rhamnosus every day for 7 days. Patients in the placebo group (n=50) received similarly administered capsules that contained Saccharum lactis. Subjective daily symptom scores for cough symptoms, nasal symptoms, pharyngeal symptoms and systemic symptoms were used as main outcome measures. The daily mean symptom score during an episode was not significantly different in the probiotic-treated group than in the control group (p>0.05). There was also a nonsignificant relative risk reduction in the number of improvement from severity symptoms score of common cold in both of groups (unadjusted absolute % reduction 0, P=1). There was no report of adverse events in the probiotic and plasebo group. In conclusion, Lactobacillus acidophilus R005 and Lactobacillus rhamnosus R0011 in the form and dosage studied do not significantly reduce the severity of symptoms of the common cold.